Study on Professors’ Perception With Respect to Higher Education Institutions’ Socially Responsible Initiatives - Adriano Stadler; Edson Andrade dos Reis; Elaine Cristina Arantes; Jansen Maia Del Corso (BBR: Brazilian Business Review)
The organization’s socially responsible actions integration and stakeholders’ demands is an increasingly encouraged practice by the market (Calabrese, Costa & Rosati, 2016). This article looks at the perception that the professor holds on the Higher Education Institution’s (HEI) socially responsible initiatives. Thus, a descriptive quantitative approach with non-probabilistic sample, accessibility and convenience was developed. The literature outlined the corporate social responsibility’s (CSR) main concepts, theories applications and stakeholders. Empirical research collected data from the HEI’s professors, through closed questionnaires. Descriptive analysis and multivariate statistics (cluster and factorial analysis) provided empirical evidence to the research. Results show the high concordance of professors in relation to the analysis categories: Economic, Legal, Ethical and Philanthropic, all of which are considered in this study, according to Carroll (2011). The sharpest legal dimension is given to the professors’ perception. Philanthropic responsibility showed the lowest agreement, coming out to the Carroll (2011) studies, which have supported this work.